2020
DOI: 10.3390/nu12020366
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Dietary Sodium, Potassium, and Sodium to Potassium Ratio with Blood Pressure—Regional Disparities in China

Abstract: High dietary sodium and low potassium intake increase blood pressure and risk of hypertension, but whether the relationship between dietary sodium and potassium and risk of hypertension is different in North China and South China remains unclear. We used data from the longitudinal China Health and Nutrition Survey (CHNS) and selected 6705 adults who participated in at least two waves in 2009, 2011, and 2015 and had no hypertension in baseline. We performed multiple linear regression analysis and multiple logis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
3
10
2
Order By: Relevance
“…Another study carried out with American adults showed that the mean population consumption was close to 3 500 mg/day, while the mean K consumption was close to 2 800 mg/day [65]. Our results did not show a high proportion between Na: K; however, other countries have shown that these proportions are above two [63,64], which was related to diastolic and systolic pressure. Mexican adults have shown to have the highest potassium consumption in the population.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Another study carried out with American adults showed that the mean population consumption was close to 3 500 mg/day, while the mean K consumption was close to 2 800 mg/day [65]. Our results did not show a high proportion between Na: K; however, other countries have shown that these proportions are above two [63,64], which was related to diastolic and systolic pressure. Mexican adults have shown to have the highest potassium consumption in the population.…”
Section: Discussioncontrasting
confidence: 69%
“…This study showed that the estimated Na intake was high (2 600 mg/day), while the (urinary) K intake was low (1 982 mg/day) [10]. A study carried out in China showed that Na consumption in the adult population was above 4 100 mg/day, while K consumption was between 1 500 and 1 600 mg / day [63]. A study carried out with Australian adults showed that the median K intake was high, since it was above 3 000 mg/day [64].…”
Section: Discussionmentioning
confidence: 67%
“…Similarly, children living in South China were less likely to be affected by hypertension, stage 1 hypertension and IDH. It has been estimated that diary sodium intake in North China is higher than that in South China, which might have attributed to the differences across geographic regions ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in a general Chinese population, which used 24 h-recall as measurement of diet electrolytes, showed similar findings for regional differences between north and south China. 16 The focus of this study: a large-scale epidemiological survey involving 130 hospitals in 23 provinces of China was conducted to examine the salt intake status of Chinese hypertensive patients. Our study also assessed salt intake levels of hypertensive patients of different ages.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in a general Chinese population, which used 24 h‐recall as measurement of diet electrolytes, showed similar findings for regional differences between north and south China. 16 …”
Section: Discussionmentioning
confidence: 99%